Choosing Family Physician: An Effective Measure for Ensuring Optimal Family Health in Ilorin Metropolis, Kwara State, Nigeria - Shehu, R. A. (International Journal of Educational Management, 2022)
This paper examined the effect of choosing family physician on overall health of the family members in Ilorin metropolis, Kwara State, Nigeria. Three hundred educated heads of families were randomly selected from the four local government areas of Ilorin metropolis (Asa, Ilorin West, Ilorin East and Ilorin South) Kwara State, Nigeria. A researcher's developed and structured questionnaire was used for data collection. Descriptive research design of the survey method was adopted for the study. Data collected were analysed with the use of frequency counts and simple percentages. The result of the study showed that the wise choice of family physician is an effective measure for ensuring optimal family health. This result also revealed that certain factors such as the credentials of the physicians, hospital affiliation, location of hospitals, mode of practice, etc. were good consideration for choosing family physicians. It was recommended that there is need to find out the credentials of the physicians before entering into contractual agreement with them. The paper also recommends that clients should determine their mode of operation before employing them. The paper also recommends that there is need to know the physician's hospitals affiliations among other things.